IMPROVING SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS FOR ORGANIZATIONAL AND TECHNOLOGICAL SOLUTIONS IN CONSTRUCTION USING MODERN INFORMATION TECHNOLOGIES: BEST PRACTICES AND STRATEGIES - Михайлик, Дмитро; Соколов, Ігор (SWorldJournal, 2025)
The article addresses current issues in improving the scientific and methodological foundations for developing organizational and technological solutions in construction projects using modern information technologies. In the context of the dynamic develop